Fra behandling til recovery. En review-studie av forskning på dagsentra for mennesker med psykiske lidelser - Bachke, Carl Christian; Larsen, Inger Beate (Nordisk Tidsskrift for Helseforskning, 2017)
This study reviews research publications topically related to day centres for people with mental health problems. The purposes are to give a general overview of the evidence-based knowledge in the field, to detect gaps of knowledge, and to throw light on the following research questions: (1) Which ideologies about day centres may be revealed in Scandinavian- and English-speaking research on day centres for people with mental health problems; and (2) What significance do the day centres have for the users? Both questions are answered by examining 34 research publications, printed in either Scandinavian or English languages during the period 1962-2015. An integrative literature review was used as method. The topical knowledge revealed is categorized under two headings: (a) the day centres’ organization, and (b) their materiality and internal life. The results and the discussion show that the day centres in the 1960s started out as arenas based on treatment ideology, dominated by psychiatric, medical knowledge. Slowly and gradually the ideology changed towards recovery approaches. However, this change in ideology does not mean that the day centres have succeeded in implementing the idea of integrating the users in the general society.